Efficiency of Production Factors in The Farming of Bird"™s Eye Chili in Lamoahi Village, North Buton Regency - Selvian, Selvian; Abdi, Abdi; Rosmawaty, Rosmawaty (Jurnal Social Economic of Agriculture, 2023)
Chili is a commodity that often triggers inflation at certain times or periods due to sudden price increases. The reason is that the availability of chilies is not sufficient for market demand due to production inefficiencies. This research aims to determine the factors that influence cayenne pepper production and determine the efficiency of using production factors using the Cobb-Douglas production function. The results of the research show that seeds and labour have a significant effect on increasing cayenne pepper farming, while land area, fertilizers, and pesticides do not have a significant effect on production. The use of production factors has not yet reached the maximum level of efficiency. Production factors that are not yet efficient are land area and labour so their utilization needs to be increased. Meanwhile, inefficient production factors are seeds, fertilizers, and pesticides so their use does not need to be increased or reduced.